Incontinentia pigmenti – a description of three cases - Laskowska, Małgorzata; Dąbkowska, Małgorzata; Szpinda-Barczyńska, Anna; Witanowska, Joanna; Zadurska, Małgorzata (Forum Ortodontyczne / Orthodontic Forum, 2018)
Incontinentia pigmenti (IP) or the Bloch-Sulzberger syndrome is a rare genetic dermatosis that occurs in females, which is classified as an ectodermal dysplasia. Papulovesicular eruptions appear on the skin in the first days of a patient’s life and then, with the lapse of time they become verrucous and hyperpigmentation lesions evolving into incontinentia pigmenti achromians. Apart from such characteristic cutaneous lesions, female patients suffering from incontinentia pigmenti may also present other cutaneous symptoms, as well as motor system and ophthalmological dysfunctions. In 54 per cent of patients dental symptoms are observed, those including mainly hypodontia, pegged teeth and delayed tooth eruption. Aim. The aim of this study was to describe three cases of female patients diagnosed with the IP syndrome who were being treated in the Department of Orthodontics of the Medical University of Warsaw. Case descriptions. Descriptions of three cases of female patients with diagnosed IP were presented. The patients had cutaneous lesions typical for IP. Medical interviews and physical examinations were conducted with them all; radiographs were performed and diagnostic casts were made. Class III malocclusions were diagnosed as well as dental abnormalities characteristic for IP (hypodontia, malformation of teeth). Conclusions. An early diagnosis allows for a child to receive a multispecialist medical and dental care. An interdisciplinary approach makes it possible to reach, functionally and esthetically, satisfactory results in the treatment and maintain patients’ teeth in good health until the period of adultness thus ensuring that the physical and mental state of female patients affected by the syndrome improves. (Laskowska M, Dąbkowska M, Szpinda- Barczyńska A, Witanowska J, Zadurska M. Incontinentia pigmenti – a description of three cases. Orthod Forum 2018; 14: 321-32).